2
$\begingroup$

Find the Fourier series for $f(\theta)=\theta^2$ and use Parseval's identity for $f$ to derive the identity:

$$\sum^\infty_{n=1} \frac{1}{n^2}=\frac{\pi^2}{6}$$

In addition, find the expansion for $f$ in terms of the functions $\{1, \cos(2\pi \theta), \sin(2\pi \theta), \cos(4\pi \theta),....\}$

Here is a link explaining Parsevals identity: https://en.wikipedia.org/wiki/Parseval%27s_identity


Can somebody help me with this one? There seems to be a lot going on and a lot of these ideas are really new to me. I'm trying to follow a proof we got in class that we can use the fourier expansion $f(x)=\theta$ on $[0,1)$ to show that

$$\sum^\infty_{n=1} \frac{1}{n^4}=\frac{\pi^2}{6}$$

But the proof is sort of confusing, and I don't see how I could adapt it. I'd really appreciate some help on this one! Thanks MSE!!

$\endgroup$
  • 2
    $\begingroup$ No need Parseval for this. See here. Maybe you wish $\sum_{n}\frac{1}{n^4}$ ? $\endgroup$ – Surb Apr 8 at 14:45
  • 1
    $\begingroup$ Why don't you post the proof that you saw in class and how you're attempting to adapt it? $\endgroup$ – cmk Apr 8 at 14:55
  • $\begingroup$ Thanks @Surb. Does that last equality somehow equal $\frac{\pi^2}{6}$?? They are close with $\frac{\pi^2}{3}$ + extra terms. $\endgroup$ – HaKuNa MaTaTa Apr 8 at 15:12
  • 1
    $\begingroup$ No it's not correct. But Parseval will help you to compute it. $\endgroup$ – Surb Apr 8 at 15:13
  • $\begingroup$ Ahh okay okay hmm interesting... I don't see a mistake in the computations though.... I'm still a little stuck, could you walk me through this? $\endgroup$ – HaKuNa MaTaTa Apr 8 at 15:15
2
$\begingroup$

You don't need Parseval (which will square your coefficients so it will give you something with $n^4$). From this question, $$ f(x)=\frac{\pi^2}{3}+4 \ \sum_{n=1}^{+\infty} \frac{(-1)^n}{n^2} \ \cos(nx). $$ As $f$ is differentiable everywhere, we have pointwise convergence. Then, evaluating at $\pi$, $$ \pi^2=f(\pi)=\frac{\pi^2}{3}+4 \ \sum_{n=1}^{+\infty} \frac{(-1)^n}{n^2} \ \cos(n\pi) =\frac{\pi^2}{3}+4 \ \sum_{n=1}^{+\infty} \frac{1}{n^2} . $$ Then $$ \sum_{n=1}^{+\infty} \frac{1}{n^2} =\frac14\,\left(\pi^2-\frac{\pi^2}3\right)=\frac{\pi^2}6. $$

If you were to use Parseval for this function, what you get is $$ \frac{2\pi^5}5=\int_{-\pi}^\pi (t^2)^2\,dt=\pi\,\left(2{a_0^2}+\sum_{n=0}^\infty a_n^2\right)=\pi\left(\frac{2\pi^4}{9}+\sum_{n=1}^\infty\frac{16}{n^4}\right). $$ Solving, you get $$ \sum_{n=1}^\infty\frac{1}{n^4}=\frac1{16}\left(\frac{2\pi^4}5-\frac{2\pi^4}9\right)=\frac{\pi^4}{90} $$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

As has been noted, Parseval with this choice of $f$ sums $\tfrac{1}{n^4}$, not $\tfrac{1}{n^2}$. So let's do the latter with Parseval on $g(\theta)=\theta$ instead. From here, $g=-2\sum_{n\ge1}\tfrac{(-1)^n}{n}\sin n\theta$, so$$\tfrac23\pi^3=\int_{-\pi}^\pi\theta^2 d\theta=4\pi\sum_{n\ge1}\tfrac{1}{n^2}\implies\sum_n\tfrac{1}{n^2}=\tfrac16\pi^2.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.